2015
DOI: 10.1080/00140139.2015.1037362
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic design and evaluation of new surgical scissors

Abstract: A new scissors handle was designed that has the eye rings modified to fit the thumb and ring finger. The newly designed scissors reduced muscle load and enabled active use of the right hand. In evaluation by surgeons, task performance improved in addition to the decrease in muscle load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Berguer and Harper conducted a unidimensional evaluation using a simple rating for factors like difficulty and cutting ability during scissor use without conducting statistical analysis [ 4 , 5 ]. Shimomura et al conducted to objectively measure the fatigue experienced by surgeons when using scissors by employing electromyography to monitor muscle activity [ 13 ]. In comparison to the studies mentioned, adopting the time-intensity analysis with two-dimensional values in our research allowed us to statistically demonstrate the reproducibility of surgeons' perceptual values.…”
Section: Discussionmentioning
confidence: 99%
“…Berguer and Harper conducted a unidimensional evaluation using a simple rating for factors like difficulty and cutting ability during scissor use without conducting statistical analysis [ 4 , 5 ]. Shimomura et al conducted to objectively measure the fatigue experienced by surgeons when using scissors by employing electromyography to monitor muscle activity [ 13 ]. In comparison to the studies mentioned, adopting the time-intensity analysis with two-dimensional values in our research allowed us to statistically demonstrate the reproducibility of surgeons' perceptual values.…”
Section: Discussionmentioning
confidence: 99%
“…Ergonomic interventions in the surgical environment are known to maximize surgical efficiency and safety [ 8 , 9 ]. Shimomura et al designed a new handle for scissors used in surgery, evaluated its effectiveness in terms of usability, and reported that this new handle design reduced muscle strain and improved work efficiency [ 20 ]. To the best of our knowledge, there have been studies of tactile sensation and ergonomic burden reduction, but no studies to date on comfort during use.…”
Section: Discussionmentioning
confidence: 99%
“…With scissors being a hand tool, the ergonomic design of scissors is of importance to their ease of use [4]. Where design-based solutions are not available, manual practice is the alternative [5].…”
Section: Introductionmentioning
confidence: 99%